Bathymetry and bed conditions of Lago Subglacial CECs, West Antarctica - A. M. Brisbourne; A. M. Smith; A. Rivera; R. Zamora; F. Napoleoni; J. A. Uribe; M. Ortega (Journal of Glaciology)
Although over 600 Antarctic subglacial lakes have been identified using radar and satellite observations, the bathymetry and bed properties, which are key to understanding conditions within the lake, have been determined in very few localities. We present measurements of water column thickness and lakebed properties from Lago Subglacial CECs (SLC), located beneath 2653 m of ice at the Rutford-Institute-Minnesota divide in Antarctica. Seismic profiles indicate a maximum water column thickness of 301.3 ± 1.5 m, at the widest part of the lake, with an estimated lake volume of 2.5 ± 0.3 km3. Seismic imaging and measurements of the reflection strength at the ice base and lakebed indicate >15 m of high-porosity fine-grained sediment in the central section of the lakebed, consistent with a depositional sequence with an age of up to 0.5 Ma. These observations, along with previous radar measurements and modelling, indicate a low-energy sedimentary environment with a long water-residence time. As such, SLC is a suitable target for exploration via direct access to recover sediment records of ice sheet and climate history and investigate microbial life with long periods of isolation.